Aspects Related to the Fraud in Procurement - Iskandar Ahmaddien (Kusuma Negara Business School, 2021)
This study intended to examine the effect of the variables of committee quality in procurement, provider quality in procurement, systems and procedures, ethics, environment, and risk assessment of fraud in procurement of goods or services at the Central Bureau of Statistics (CBS). This study utilized a survey method by distributing questionnaires at the Directorate of Asset Management and Maintenance in CBS by involving Commitment Making officials (CMO). Subsequently, collected information was analyzed by using multiple regression in the Lisrel application. The results of this study showed that the quality of the committee, the quality of provider and the environment in procurement provides a significant influence on fraud in the procurement of goods and services, while systems and procedures, ethics and risk assessments do not contribute significantly on fraud in procurement of goods or services.